Maironis as a Man of Books: the Ontologization of Culture in the Works and Egodocuments of Maironis - Žmuida, Eugenijus (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]The national poet Maironis is best known as the reformer of versification, the creator of normative language. Nevertheless, his first book was dedicated to the history of Lithuania and was extremely important in the 19th century, when history was supposed to be the most important science, and when all the European nations were concerned to have books written on the subject of national history. Many authors in Lithuania wrote on history, but only the book of Maironis, published in 1891, presented a new model of Lithuanian history, breaking the stereotype that had dominated the field for many centuries. He replaced the elegiac vision of history with an optimistic, forward-looking picture, predicting the cultural renaissance of the nation. In the second edition (1906), by adding a short history of Lithuanian literature, taking part in new periodicals, discussing cultural concerns in correspondence and writing new fictional and science works, Maironis practically realized his cultural-philosophical aims and these activities frequently served as examples for the younger generations of artists. His model of history, also of history of literature, his optimistic vison regarding the future became a common average of the awareness of the nation, and this great contribution of Maironis to the formation of the present Lithuanians is often forgotten. The goal of this article is to revive the relationship with Maironis.